Correlation between DNA damage responses of skin to a test dose of radiation and late adverse effects of earlier breast radiotherapy. Issue 2 (May 2016) - Somaiah, Navita; Chua, Melvin L.K.; Bourne, Sara; Daley, Frances; A' Hern, Roger; Nuta, Otilia; Gothard, Lone; Boyle, Sue; Herskind, Carsten; Pearson, Ann; Warrington, Jim; Helyer, Sarah; et al.
Abstract: Aim: To correlate residual double strand breaks (DSB) 24 h after 4 Gy test doses to skin in vivo and to lymphocytes in vitro with adverse effects of earlier breast radiotherapy (RT). Patients and methods: Patients given whole breast RT ⩾5 years earlier were identified on the basis of moderate/marked or minimal/no adverse effects despite the absence ('RT-Sensitive', RT-S) or presence ('RT-Resistant', RT-R) of variables predisposing to late adverse effects. Residual DSB were quantified in skin 24 h after a 4 Gy test dose in 20 RT-S and 15 RT-R patients. Residual DSB were quantified in lymphocytes irradiated with 4 Gy in vitro in 30/35 patients. Results: Mean foci per dermal fibroblast were 3.29 (RT-S) vs 2.80 (RT-R) ( p = 0.137); 3.28 (RT-S) vs 2.60 (RT-R) in endothelium ( p = 0.158); 2.50 (RT-S) vs 2.41 (RT-R) in suprabasal keratinocytes ( p = 0.633); 2.70 (RT-S) vs 2.35 (RT-R) in basal epidermis ( p = 0.419); 12.1 (RT-S) vs 10.3 (RT-R) in lymphocytes ( p = 0.0052). Conclusions: Residual DSB in skin following a 4 Gy dose were not significantly associated with risk of late adverse effects of breast radiotherapy, although exploratory analyses suggested an association in severely affected individuals. By contrast, a significant association was detected based on the in vitro response of lymphocytes.